A study into shared reading groups, with specific relation to religious reading - Harsh, Esther Valora (Frontiers in Psychology, 2022)
Abstract This paper examines a live shared-reading group conducted through The Reader Organisation, by approval of the University of Liverpool’s ethics committee. The intention in forming the group was to explore the reading of Marilynne Robinson’s Home by a wide variety of modern readers of different backgrounds and persuasions, in the light of religious writing in an age of diminished religious tradition. The main research question was to test what literature is able to do in carrying meaning which can be seen as religious, or was previously deemed religious, amongst readers who may not think of themselves in such terms. The second was to see how a shared community-group setting can enable collaborative engagement with the challenge to develop different ways of thinking, beyond the individual default of either religious dogma or anti-religious prejudice. Acting as the reader leader of the group, the researcher brings developed tools taken from psychologist Wilfred Bion and William James, introduced to the reading group as ways of measurement and navigation through the novel. The method employed in this study is grounded theory. If the aim was simply to undertake a study of the text then this paper would be more narrowly literary, but the concern was with wider real-world effects in relation to individuals within the group-work. Grounded theory, in refusing to begin from rigidly preassembled categories, is appropriate to a literature-inflected study, and in particular a literary study that is concerned with religious meaning in a secular setting. Through close examination of the week by week transcripts of the reading group, this paper highlights the search for moments of development, or what might have stood in the way of development. One of the most fascinating findings in this study is what will be called the mini-traditions developed by the group members in praxis, which they use and come back to during their work with the more difficult and painful passages.